2000
DOI: 10.1111/j.1572-0241.2000.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of TT virus infection in blood donors with elevated ALT in the absence of known hepatitis markers

Abstract: Although TTV is not likely to explain the majority of elevated ALT cases in otherwise healthy blood donors, TTV infection may potentially be associated with some cases. Based on these findings, we propose that the role of TTV in the pathogenesis of acute and chronic liver diseases merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Zhao et al 14 and Moriyama et al 15 reported that TTV co-infection did not modify the serology or biochemical markers of chronic hepatitis B and C. However, few workers have reported increased severity of biochemical and histologic parameters of liver damage in hepatitis C patients co-infected with TTV. 16 In our study, TTV viraemia was associated with raised serum bilirubin, AST, ALT and alkaline phosphatase levels in only 1%, 2%, 4% and 1% healthy individuals respectively. Dai et al 17 investigated the prevalence and effects of TTV infection on liver function tests in patients with negative hepatitis B and hepatitis C viral markers.…”
Section: [ ( F I G _ 3 ) T D $ F I G ]contrasting
confidence: 45%
“…Zhao et al 14 and Moriyama et al 15 reported that TTV co-infection did not modify the serology or biochemical markers of chronic hepatitis B and C. However, few workers have reported increased severity of biochemical and histologic parameters of liver damage in hepatitis C patients co-infected with TTV. 16 In our study, TTV viraemia was associated with raised serum bilirubin, AST, ALT and alkaline phosphatase levels in only 1%, 2%, 4% and 1% healthy individuals respectively. Dai et al 17 investigated the prevalence and effects of TTV infection on liver function tests in patients with negative hepatitis B and hepatitis C viral markers.…”
Section: [ ( F I G _ 3 ) T D $ F I G ]contrasting
confidence: 45%
“…However, the evidence is not totally unequivocal, since data also exist that are compatible with the possibility that, in some cases, transient and mild abnormalities in liver enzyme levels are associated with TTV infection (33,34,56,61,65,68,81,88,110,126). Likewise, in several series of HCV patients, coinfection with TTV appeared to be associated with increased severity of biochemical and histological parameters of liver damage (15,22,48,56,172,175,191). In a series of 26 patients with fulminant liver failure studied by Tanaka et al (163), mortality was 100% in TTV-infected patients versus less than 50% in uninfected ones.…”
Section: Clinical Significancementioning
confidence: 93%
“…Furthermore, it has been reported that chronically infected individuals harbor high levels of mature TTV DNA as well as replicative DNA intermediates and mRNA in all body sites examined (23) except the central nervous system (14), thus implying that TTV is polytropic in nature or grows in a cell type(s) that is represented throughout the human body. With regard to pathogenesis, early indications that TTV might cause some forms of cryptogenetic hepatitis have been questioned (7,20) while attempts to link the virus to other diseases have either been unsuccessful or need confirmation (5, 38), leaving the virus with "orphan" status with regard to clinical disease.Thus far, the routes of TTV entry into the body, the locations of initial virus amplification before infection becomes systemic, and the clinical consequences of primary infection, if any, have been investigated only to a limited extent. In this study we have approached these issues by examining children with acute respiratory infections (ARD).…”
mentioning
confidence: 99%
“…The taxonomy of the vast array of related viral agents that have been identified in humans since the first description of TTV by Nishizawa et al in 1997 (21) is also uncertain. Recently, however, Okamoto and Mayumi (22) have divided TTV isolates into at least four phylogenetic clusters differing by over 40% at the nucleotide level: group 1 has the original TTV isolate as the prototype and includes genotypes 1 to 6; group 2 has PMV as the prototype and comprises genotypes 7,8,17,22, and 23; group 3 has SANBAN and SENV as representative isolates and includes genotypes 9 to 16 and 18 to 20; and group 4 has YONBAN as the prototype and includes genotype 21. Furthermore, while the present report was in preparation, the same group identified several novel genotypes within group 4 TTV as well as members of a proposed fifth group (26).…”
mentioning
confidence: 99%